The effectiveness of the auditory steady state response in diagnosing hearing loss in infants - De Wet Swanepoel; Dunay Schmulian; René Hugo (AOSIS, 2002)
This paper aims to provide a review of the emerging Auditory Steady State Response in light of existing procedures for diagnosis of hearing loss in infants. Opsomming Hierdie artikel poog om 'n oorsig te verskaf van die opkomende Ouditief Standhoudende Respons teenoor huidige prosedures wat gebruik word om gehoorverlies in babas en jong kinders te diagnoseer. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.